Implementasi Pendidikan Holistik dalam Pembelajaran Pendidikan Agama Islam di SMA Negeri Plus Provinsi Riau - Nur Zakiyah; Zaitun Zaitun (AL-FIKRA, 2021)
This research aimed at knowing the implementation of holistic education in Islamic Education subject at State Senior High School Plus Riau Province. The subjects of this research were a headmaster, an Islamic Education subject teacher. The object was the implementation of holistic education in Islamic Education subject at State Senior High School Plus Riau Province. a headmaster, and an Islamic Education subject teacher were the population of this research. All of them were selected as the samples. Observation, Interview, and documentation were the techniques of collecting data. The technique of analyzing data was quantitative descriptive. Calculating the data obtained through questionnaire and interview was done manually. The results were to get the data of the implementation of holistic education in Islamic Education subject at State Senior High School Plus Riau Province. Based on the data analysis, it was obtained that the implementation of holistic education in Islamic Education subject at State Senior High School Plus Riau Province was on very good category because the final percentage score was 85.30%, it was on the range scores of 81%-100%, and it meant that it was very good. The factors supporting the teacher effort in implementing holistic education in Islamic Education subject at State Senior High School Plus Riau Province were school culture, teachers, students, collaboration, facilities and infrastructure, and evaluation.